2016
DOI: 10.1177/1060028016644466
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use and Recurrent Falls in Community-Dwelling Older Adults

Abstract: Background Few studies have compared the risk of recurrent falls across various antidepressant agents—using detailed dosage and duration data—among community-dwelling older adults, including those who have a history of a fall/fracture. Objective To examine the association of antidepressant use with recurrent falls, including among those with a history of falls/fractures, in community-dwelling elders. Methods This was a longitudinal analysis of 2948 participants with data collected via interview at year 1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 33 publications
2
58
2
Order By: Relevance
“…29-31 Additionally, there is some evidence of an association between SSRIs and increased risk of falls and fractures, suggesting that we may be observing a risk factor for TBI, although our study did not examine this question. 32,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29-31 Additionally, there is some evidence of an association between SSRIs and increased risk of falls and fractures, suggesting that we may be observing a risk factor for TBI, although our study did not examine this question. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…25 Older adults are more likely to initially consult with a primary care provider for psychological problems and receive a psychiatric diagnosis from a non-specialty setting. 32 However, these providers may not feel comfortable prescribing psychotropic medications following TBI in the absence of evidence based recommendations. 11,12,35 The disparity may also result from the perception that a psychological reaction to trauma is expected and will resolve on its own without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Use of antidepressants, particularly SSRIs, has been consistently found to be associated with increased risks of falls and recurrent falls [40][41][42][43]. For example, in a longitudinal analysis of 2948 community-dwelling older adults followed-up for 7 years, antidepressant users, compared with nonusers, were observed to have a 48% greater likelihood of recurrent falls (OR 1.48, 1.12-1.96), particularly those taking SSRIs with an OR of 1.62 (1.15-2.28) [40]. Alike, in a cross-sectional survey including community-dwelling older adults from Australian general practices, antidepressants use was independently associated with multiple falls (OR 1.46, 1.25-1.70).…”
Section: 80mentioning
confidence: 99%
“…Several studies have found an association between the use of all antidepressants, particularly SSRIs, and falls and fractures in older adults 99100. An older longitudinal analysis (1997-2004) of 2948 older people living in the community found an adjusted odds ratio of 1.62 (1.15 to 2.28) for SSRIs and 1.48 (1.12 to 1.96) for antidepressants overall 101. However, most evidence to date comes from observational studies; and use of antidepressants and falls are both common in this patient population, so causation cannot be inferred 102…”
Section: Interventions In Primary Carementioning
confidence: 99%